2019
DOI: 10.3390/app9112338
|View full text |Cite
|
Sign up to set email alerts
|

Computer Aided Design to Produce High-Detail Models through Low Cost Digital Fabrication for the Conservation of Aerospace Heritage

Abstract: Aerospace heritage requires tools that allow its transfer and conservation beyond photographs and texts. The complexity of these engineering projects can be collected through digital graphic representation. Nevertheless, physical scale models provide additional information of high value when they involve full detailed information, for which the model in engineering was normally one more product of the manufacturing process, which entails a high cost. However, the standardization of digital fabrication allows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Regarding topics, the predominance of an architecture research field concerning its artistic nature has been confirmed, in which the most repeated concepts are art, form, idea or drawing. Meanwhile, digital manufacturing is one of the graphic analysis research fields that architects are not exploring and that could be used to manufacture high-detail models [49], to produce ephemeral elements [52] or to develop mechanical prototypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding topics, the predominance of an architecture research field concerning its artistic nature has been confirmed, in which the most repeated concepts are art, form, idea or drawing. Meanwhile, digital manufacturing is one of the graphic analysis research fields that architects are not exploring and that could be used to manufacture high-detail models [49], to produce ephemeral elements [52] or to develop mechanical prototypes.…”
Section: Discussionmentioning
confidence: 99%
“…The third field incorporates the topics of design and manufacturing (see Table 3). Research is related to the process and the possibilities of modeling through CAD software, and its subsequent materialization through digital manufacturing [47], the design of methods for the automatic analysis of the parts that will be physically obtained after modeling to improve performance for subsequent uses [48], the preservation of aerospace heritage through low-cost manufacturing techniques for high-precision models [49] (see Figure 3), 3D scanning for the production of elements, such as prostheses [50], or food to design its packaging [51], and even the generation of ephemeral architecture [52]. Table 3.…”
Section: Design and Manufacturingmentioning
confidence: 99%
“…For this modelling phase, the Sketcher and Part Design modules of CATIA V5 were applied. These 3D CAD modelling techniques provide a fundamental tool in the process of designing of technical historical heritage, for example, in aerospace heritage [33], as a previous stage of CAE (computer-aided engineering) analysis [34,35] and, in general, as an application for any example of cultural heritage [36].…”
Section: Sizing Design and Assembly Of The Elements Of The Isochronmentioning
confidence: 99%
“…Fusion 360 combines 3D modeling with the advantages of cloud computing tools ( Figure 1) through cloud-stored files in the Autodesk cloud (called A360). It naturally allows collaborative 3D modeling, which is appropriate for educational environments and fab labs [18]. Rassovytska and Striuk analyzed the suitability of cloud tools for the professional activity of mechanical engineers [22].…”
Section: Introductionmentioning
confidence: 99%